Frequency of Various Skin Diseases in Patients Visiting the OPD of Dermatology Department at a Tertiary Care Hospital - Syed Bilal Ahmed, Neelam Ayub, Muhammad Uzair, Zafar Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The largest organ in the body is the skin. It is impacted by a number of diseases, such as genodermatoses, inflammatory diseases, infections, metabolic abnormalities, and neoplastic diseases, much like every other organ. Objective: To determine the prevalence of various skin diseases in patients visiting the OPD of dermatology department at a tertiary care Hospital Methodology: The current cross-sectional study was carried out at the Dermatology department PGMIQ/ BMC Hospital Quetta. The study duration was six months from January 2023 to June 2023. The overall sample size in our study was 500 based on the WHO sample size calculator. The inclusion criteria were all the patients of both the gender and all ages visiting the OPD of Dermatology department PGMIQ/ BMC Hospital Quetta. Skin conditions were divided into infectious and non-infectious categories. Version 23 of the Statistical Package for Social Sciences (SPSS) was used to analyze the data. Results: In the current study, a total of 500 patients were enrolled. The male patients were 210 (42%) while female patients were 290 (48%). The frequency of infective diseases was 225 (45%) while non-infective diseases were 275 (55%). The distribution based on infective diseases shows that the most frequent condition was scabies in 170 (34%) patients followed by fungal infections in 25 (5%) patients, Warts in 15 (3%) patients and Impetigo in 15 (3%) patients. The distribution of non-infective diseases shows that the most frequent condition was Acne in 90 (18%) patients followed by melasma in 50 (10%) patients, alopecia areata in 25 (5%) patients and psoriasis in 20 (4%) patients. Conclusion: Non-infectious skin disorders were more common, according to our research. The most prevalent dermatosis was scabies. Our investigation revealed eczema and fungal infections, the causes of which might be attributed to poverty, occupational features, and overcrowding, which can all contribute to an elevated illness burden. A campaign to raise public awareness is necessary, and prompt reporting and treatment of skin conditions are crucial to reduce the prevalence of skin diseases and enhancing quality of life. Keywords: Frequency; Skin diseases; Scabies; Dermatosis